Meaning in life and demoralization: a mental-health reading perspective of suicidality in the time of COVID-19 - Costanza, Alessandra; Di Marco, Sarah; Burroni, Marta; Corasaniti, Francesco; Santinon, Patrizia; Prelati, Massimo; Chytas, Vasileios; Cedraschi, Christine; Ambrosetti, Julia (Acta Biomedica Atenei Parmensis, 2020)
Consequences on mental health have been reported in general population, vulnerable individuals, psychiatric patients, and healthcare professionals. It is urgently necessary to study mental health issues in order to set priorities for public health policies and implement effective interventions. Suicidality is one of the most extreme outcomes of a mental health crisis. It is currently too early to know what the effect of COVID-19 will be on suicidality. However, authoritative commentary papers alert that most of the factors precipitating suicide are, and probably will be for a long time, present at several individual existence levels. A number of prevention measures and research considerations have been drawn up. A point of the latter, recommended by the International COVID-10 Suicide Prevention Research Collaboration, states that “the COVID-19 suicide research response should be truly multidisciplinary. This will foster research that addresses the different aspects and layers of risk and resilience.It will also foster research that informs prevention efforts by taking a range of perspectives” (Niederkrotenthaler et al., 2020). In this light, we would like to propose a reading perspective of suicidality that takes into account Meaning in Life (MiL) and demoralization. Both of the constructs were studied in heterogeneous populations with extreme life situations having led to a fracture between a “before” and an “after”, and play a role in affecting suicidality, respectively as resilience and risk factors. In clinical practice, during these unprecedent times, we wish that this more inclusive approach could: 1) contribute to prevention, by delineating more individualized suicidal risk profiles in persons conventionally non-considered at risk but here exposed to an extremely uncommon experience, 2) enrich supportive/psychotherapeutic interventions, by broadening the panel of means to some aspects constitutive of the existential condition of a person who is brutally confronted with something unexpected, incomprehensible and, in some ways, still unpredictable.